2015
DOI: 10.1248/bpb.b15-00402
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin Inhibits Renal Urate Reabsorption by Modulating Urate Transporters in Experimental Hyperuricemia

Abstract: Mangiferin, a natural glucosyl xanthone from the leaves of Mangifera indica L., was previously shown to exert potent hypouricemic effects associated with inhibition of the activity of xanthine dehydrogenase/ oxidase. The present study aimed to evaluate its uricosuric effect and possible molecular mechanisms underlying the renal urate transporters responsible for urate reabsorption in vivo. Mangiferin (1.5-24.0 mg/kg) was administered intragastrically to hyperuricemic mice and rats induced by the intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Therefore, increased FEUA can be interpreted as the increased excretion of renal uric acid. In the present study, uric acid levels in urine and FEUA reduced in the PO group compared to the NC group although there are reports demonstrating the uricosuric effect of PO [33, 34]. This observation is in agreement with finding of various reports [33, 34].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, increased FEUA can be interpreted as the increased excretion of renal uric acid. In the present study, uric acid levels in urine and FEUA reduced in the PO group compared to the NC group although there are reports demonstrating the uricosuric effect of PO [33, 34]. This observation is in agreement with finding of various reports [33, 34].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, uric acid levels in urine and FEUA reduced in the PO group compared to the NC group although there are reports demonstrating the uricosuric effect of PO [33, 34]. This observation is in agreement with finding of various reports [33, 34]. This discrepancy might be associated with the differences in approaches for administration periods and collecting time of urine.…”
Section: Discussionsupporting
confidence: 90%
“…We found that MG attenuated proteinuria and renal pathological damage, including deposition of IgG and C3, and improved renal function as well. The beneficial effects of MG on renal function have also been reported in multiple kidney injury models, such as chronic nephritis, acute renal injury [22,23], experimental hyperuricemia [24] and diabetic nephropathy [25,26], indicating that MG preserves renal function through a variety of mechanisms. Since many autoimmune diseases, including LN, are accompanied with a significant increase in serum autoantibodies, we determined whether MG would regulate autoantibody responses in B6/gld mice.…”
Section: Foxp3mentioning
confidence: 89%
“…However, attenuating the production of IL‐6, it potentially blocks the phosphorylation of JNK and p38, downstream of these signaling molecules, different apoptosis regulatory signals are activated . In another study with experimental model of hyperuricemia, mangiferin is shown to modulate the activity of the urate transporter and blocks the reabsorption of urate in the renal tissue , facilitating the excretion of uric acid. Different clinical studies suggest that acute renal injury is a common complication arising during the treatment of sepsis .…”
Section: Effect Of Mangiferin Against Inflammation Related Organ Dysfmentioning
confidence: 99%